Increasing student engagement and retention in e-learning environments Web 2.0 and blended learning technologies - Wankel, Charles; Blessinger, Patrick (Cutting-edge technologies in higher education, 2013)
Increasing Student Engagement and Retention in e-Learning Environments: Web 2.0 and Blended Learning Technologies examines new research on how online and blended learning technologies are being used in higher education to increase learner engagement in an era of increasing technological convergence and dependence. These enabling technologies are reshaping and reframing the practice of teaching and learning in higher education. Through case studies, surveys, and literature reviews, this volume will examine online and blended technologies are being used to improve academic literacies in students, to create engaging communities of practice, and how these technologies are being used to improve learner motivation and self-empowered learners. This volume will also discuss a framework for adopting and deploying these technologies.